Determinants of Investment Risk on Stock Performance in the Food and Beverage Industry in the Indonesian Capital Market - Djayani Nurdin; Muhamad Yunus Kasim; Munawarah, Munawarah; Suhatman, Suhatman (Universitas Muhammadiyah Palu, 2024)
This studi aims to determine the influence of investment risk on stock prices in food and beverage sub-sector manufacturing companies listed on the Indonesian Stock Exchange in 2018-2022. The population of this study were food and beverage sub-sector companies listed on the Indonesian Stock Exchange in 2018-2022. The sampling technique used purposive sampling and obtained a sample of 55 observational data from 11 companies. Methods of data collection using documentation technique. Research data were analyzed using the regression data panel method. The result showed that the market risk variable had an insignificant positive effect on stock prices, the business risk variabel had a significant negative effect on stock prices and the financial risk variable had a significant negative effect on stock prices. While simultaneously the independent variables have a significant influence on stock prices.